Predictability of stock returns using financial statement information: Evidence on semi-strong efficiency of emerging Greek stock market - Alexakis, C.; Patra, T.; Poshakwale, Sunil S. (Taylor & Francis, 2010)
This article examines the predictability of stock returns in the Athens Stock Exchange (ASE) during 1993 to 2006 by using accounting information. Using panel data analysis, this article concludes that the selected set of financial ratios contains significant information for predicting the cross-section of stock returns. Results indicate that portfolios selected on the basis of financial ratios produce higher than average returns, suggesting that the emerging Greek market does not fully incorporate accounting information into stock prices and hence it is not semi-strong efficient.